Multi-match Packet Classification on Memory-Logic Trade-off FPGA-based Architecture - Zerbini, Carlos A.; Finochietto, Jorge M. (2022)
Fil: Zerbini, Carlos A. Universidad Tecnológica Nacional. Departamento de Ingeniería Electrónica; Argentina.